Attitudes toward the Canadian Guideline for Safe and Effective Use of Opioids for Chronic Non-Cancer Pain: A qualitative study - Chang, MSc, Yaping; Zhu, Kan Lun; Florez, MD, MSc, Ivan D.; Cho, BHSc, Sung Min; Zamir, HBSc, Nasim; Toma, BESc, Augustin; Mirza, MD, Reza Donald; Guyatt, MD, MSc, Gordon H.; Buckley, MD, Norman; Busse, DC, PhD, Jason W. (Journal of Opioid Management, 2016)
Background: Chronic noncancer pain (CNCP) refers to all pain disorders, not due to cancer, that persist for ≥3 months. The point prevalence of CNCP in the general population of Western countries is between 19 and 33 percent. Opioids are commonly prescribed for CNCP and are associated with both benefits and harms. The Canadian Guideline for Safe and Effective Use of Opioids for CNCP was published in 2010 to provide guidance for optimal opioid prescribing in patients with CNCP. Objectives: To investigate the attitudes toward, and use of, the Canadian Opioids Guideline among pain physicians. Design: A qualitative study using one-on-one, semistructured interviews with 12 pain physicians in Ontario, Canada, and thematic analysis of verbatim transcripts. Results: Major themes that emerged from interviews included: (1) generally positive attitudes toward the 2010 Canadian Opioids Guideline, but limited use—half (six of 12) reported they did not use the guideline in practice; (2) strongly contrasting views regarding the 200 mg/d morphine equivalent watchful dose; (3) recognition of gaps in the guideline, especially recommendations for urine drug screening and pain severity-specific therapy; (4) the guideline is excessively long and the format suboptimal; and (5) improved dissemination and education are needed to enhance guideline uptake. Conclusions: Despite its merits, the Canadian Opioids Guideline suffers from information gaps and from limited uptake, at least in part due to suboptimal format and suboptimal dissemination.